The Fiber Cell-Specific Overexpression of COMT2 Modulates Secondary Cell Wall Biosynthesis in Poplar - Hanyu Chen; Hong Wang; Zhengjie Zhao; Jiarui Pan; Yao Yao; Yihan Wang; Keming Luo; Qin Song (Plants)
Wood, as a natural and renewable resource, plays a crucial role in industrial production and daily life. Lignin, as one of the three major components of the plant cell secondary wall, plays a key role in conferring mechanical strength and enhancing stress resistance. The caffeic acid-O-methyltransferase (COMT) family of oxygen-methyltransferases is a core regulatory node in the downstream pathway of lignin biosynthesis. Here, our report shows that caffeic acid-O-methyltransferase 2 (COMT2) exhibits high conservation across several species. Tissue expression analysis reveals that COMT2 is specifically highly expressed in the secondary xylem of Populus tomentosa stems. We demonstrated that the specific overexpression of COMT2 in fiber cells of Populus tomentosa led to a significant increase in plant height, stem diameter, internode number, and stem dry weight. Furthermore, we found that the specific overexpression of COMT2 in fiber cells promotes xylem differentiation, lignin accumulation, and the thickening of the secondary cell wall (SCW) in fiber cells. Our results indicate that key downstream lignin biosynthesis enzyme genes are upregulated in transgenic plants. Additionally, mechanical properties of stem bending resistance, puncture resistance, and compressive strength in the transgenic lines are significantly improved. Moreover, we further created the DUFpro:COMT2 transgenic lines of Populus deltoides × Populus. euramericana cv ‘Nanlin895’ to verify the functional conservation of COMT2 in closely related poplar species. The DUFpro:COMT2 Populus deltoides × Populus. euramericana cv ‘Nanlin895’ transgenic lines exhibited phenotypes similar to those observed in the P. tomentosa transgenic plants, which showed enhanced growth, increased lignin accumulation, and greater wood strength. Overall, the specific overexpression of the caffeic acid O-methyltransferase gene COMT2 in poplar stem fiber cells has enhanced the wood biomass, wood properties, and mechanical strength of poplar stems.